Pathogenic variants in KCNQ2 cause intellectual deficiency without epilepsy: Broadening the phenotypic spectrum of a potassium channelopathy. Issue 6 (23rd March 2021) - Mary, Laura; Nourisson, Elsa; Feger, Claire; Laugel, Vincent; Chaigne, Denys; Keren, Boris; Afenjar, Alexandra; Billette, Thierry; Trost, Detlef; Cieuta‐Walti, Cécile; Gerard, Bénédicte; Piton, Amélie; et al.
Abstract: High‐throughput sequencing (HTS) improved the molecular diagnosis in individuals with intellectual deficiency (ID) and helped to broaden the phenotype of previously known disease‐causing genes. We report herein four unrelated patients with isolated ID, carriers of a likely pathogenic variant in KCNQ2, a gene usually implicated in benign familial neonatal seizures (BFNS) or early onset epileptic encephalopathy (EOEE). Patients were diagnosed by targeted HTS or exome sequencing. Pathogenicity of the variants was assessed by multiple in silico tools. Patients' ID ranged from mild to severe with predominance of speech disturbance and autistic features. Three of the four variants disrupted the same amino acid. Compiling all the pathogenic variants previously reported, we observed a strong overlap between variants causing EOEE, isolated ID, and BFNS and an important intra‐familial phenotypic variability, although missense variants in the voltage‐sensing domain and the pore are significantly associated to EOEE ( p < 0.01, Fisher test). Thus, pathogenic variants in KCNQ2 can be associated with isolated ID. We did not highlight strong related genotype–phenotype correlations in KCNQ2‐ related disorders. A second genetic hit, a burden of rare variants, or other extrinsic factors may explain such a phenotypic variability. However, it is of interest to study encephalopathy genes in non‐epileptic ID patients.